Bottom trawl fishing footprints on the world's continental shelves - Amoroso, R.; Pitcher, C.; Rijnsdorp, A.; McConnaughey, R.; Parma, A.; Suuronen, P.; Eigaard, O.; Bastardie, F.; Hintzen, N.; Althaus, F.; Baird, S.; Black, J.; et al. (National Academy of Sciences, 2018)
© 2018 National Academy of Sciences. All rights reserved. Bottom trawlers land around 19 million tons of fish and invertebrates annually, almost one-quarter of wild marine landings. The extent of bottom trawling footprint (seabed area trawled at least once in a specified region and time period) is often contested but poorly described. We quantify footprints using high-resolution satellite vessel monitoring system (VMS) and logbook data on 24 continental shelves and slopes to 1,000-m depth over at least 2 years. Trawling footprint varied markedly among regions: from < 10% of seabed area in Australian and New Zealand waters, the Aleutian Islands, East Bering Sea, South Chile, and Gulf of Alaska to > 50% in some European seas. Overall, 14% of the 7.8 million-km2 study area was trawled, and 86% was not trawled. Trawling activity was aggregated; the most intensively trawled areas accounting for 90% of activity comprised 77% of footprint on average. Regional swept area ratio (SAR; ratio of total swept area trawled annually to total area of region, a metric of trawling intensity) and footprint area were related, providing an approach to estimate regional trawling footprints when highresolution spatial data are unavailable. If SAR was =0.1, as in 8 of 24 regions, therewas > 95% probability that > 90%of seabed was not trawled. If SAR was 7.9, equal to the highest SAR recorded, there was > 95% probability that >70% of seabed was trawled. Footprints were smaller and SAR was =0.25 in regions where fishing rates consistently met international sustainability benchmarks for fish stocks, implying collateral environmental benefits from sustainable fishing.